Nilai Budaya Pada Novel Gugur Bunga Kedaton Karya Wahyu H.R: Kajian Antropologi Sastra Dan Implementasinya Dalam Pembelajaran Sastra Di Sma - Ayuningtyas, Dian (2016)
This study has four objectives. Describe the social background of historical authorship of Wahyu H.R. Describe the structure builders novel GBK work of Wahyu H.R. Describe the cultural values embodied in the novel GBK work of Wahyu H.R. Explained implementation of novel research results GBK of Wahyu H.R work in teaching literature in high school. This study uses descriptive qualitative method. Object of research is cultural values contained in the novel GBK of Wahyu H.R with a review of the anthropological literature. The data in this study a paragaf, sentences, and words related to novel structures and cultural values. The primary data source in this study is novel GBK. While secondary data sources in the research is a biography of the author and literary authors. Data collection techniques used are literature, see, and record. Validation data using triangulation theory. Data were analyzed using heuristic and hermeneutic reading method. In the novel there are five cultural values were analyzed using the theory presented by Djamaris. This value includes the value of culture in the human relationship with God which consists of the value ketawakalan, piety, faith in destiny, grateful, and pleasure, the value of culture in human relationships with the society of the value of consensus, mutual cooperation, harmony or balance, and solidarity ,cultural values in human relationships with others that consist of the value of love, loyalty, obedience to parents, and wisdom, the value of culture in the human relationship with yourself that consists of the value of willpower, study, live custom and religion, courage and vigilance, and cultural values in human relationships with nature consisting of human values that unite with nature and human nature conquered or utilize. Implementation of cultural value in GBK novel as literature in high school teaching materials appropriate and relevant learning materials to be used as literature. GBK novel contains elements of intrinsic and extrinsic elements. Intrinsic element is implemented to the students to find a theme, a fact the story and the story means. Extrinsic elements of the novel are implemented to discover cultural values contained in the novel.